Effects of pulsed ultrasound on Escherichia coli and Staphylococcus aureus - SESAL, NÜZHET CENK (OXFORD UNIV PRESS, 2014)
Background: Common disinfection methods like biocides, ultraviolet light and heat treatment are not efficient enough to succeed in bacterial inactivation for some microorganisms have become resistant to them. The aim of this study was to obtain information about the effect of pulsed ultrasound sonication with 30 kHz frequency and 100 W power on the inactivation capability of two bacteria groups, namely Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923, in physiological water samples. Methods: The ultrasonic irradiation of bacterial samples with different populations of 5x10(3), 1.5x10(4) and 3x10(4) cfu/ml was performed at constant frequency with various treatment times. The specific energies (gamma) were calculated for these different concentrations of E. coli and S. aureus. The rate constant of ultrasonic inactivation was estimated in the linear region of the plot representing survival ratio logarithm vs sonication time. Results: While a significant death rate for E. coli was observed by ultrasonic treatment, contrary to expectation, an increase in S. aureus populations was observed. Conclusions: Considering the widespread use of ultrasound for the sterilization of tools and equipment used in hospitals, the obtained results indicate that ultrasound sonication is not a suitable method for the elimination of S. aureus, a major hospital pathogen.
Keywords: Bacteria inhibition; Escherichia coli; Pulsed ultrasound; Specific energy; Staphylococcus aureus; Ultrasonic irradiation; DISINFECTION; INACTIVATION